Understanding on Online Assessments for EFL Learning During Covid-19 Pandemic - Ratini Setyowati; Sopingi; Indra Hastuti (LPPM Universitas Duta Bangsa Surakarta, 2021)
Covid-19 as the global pandemic with social and physical distancing consequence has affected educational practices. Amidst the Covid-19 Pandemic, Schools are temporally closed therefore, students study at home, teacher adapts the situation. They have online class and online assessment as well. In this case, technology supports teaching learning process. The purpose of the study is to understand some types of Online English Assessments for during Covid-19 Pandemic. Data were collected from books, journals, news, social media and other relevant sources. Literature study is carried out to obtain the necessary data by reading the literature sources. The data collected was then analyzed qualitatively. The result of the study is Teacher can assess the EFL learning by using formative assessment, the assessment can assess reading, speaking, writing and grammar by give task activities. Beside that synchronous method is the most proper one. Teacher can use some applications that can meet the students virtually like Google meets, Zoom Meeting and other synchronous application.